KONTRIBUSI PAJAK REKLAME DAN PAJAK PERHOTELAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KUTAI BARAT - -, Helmi - (EKONOMIA, 2015)
This study aimed to determine the contribution of advertisement tax and hospitality tax on revenue West Kutai. As this study were analyzed using multiple linear regression analysis models were performed with SPSS version 11.5 software with data retrieval based on secondary data advertisement tax, hotel tax and local revenues from the Department of Revenue West Kutai District 2003 to 2011.Based on the model of multiple linear regression analysis showed that the independent variable (advertisement tax and motel tax) together give a significant effect on revenue as it shows that the probability of the F-statistic value is smaller than the significance level used (0.032 <0, 05).The largeR-squared (R2) of 0.682 is obtained show that the model can explain the strong association between exogenous variables (advertisement tax and hotel tax) on endogenous variables (revenue) of 68.2 percent. The remaining 31.8 percent is influenced by other variables that are outside of this equation. Advertisement tax has significant influence but not on revenue because it shows that the probability of the t-statistic greater than the significance level used is (0.078> 0.05). Furthermore hospitality tax also has a significant influence but not on revenue because it shows that the probability value of t-statistic greater than the significance level used is (0.867>0.05).